2023
DOI: 10.3390/ijms241914612
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the Target Traumatic Brain Injury Population for Hyperbaric Oxygen Therapy

Samantha Schimmel,
Bassel El Sayed,
Gavin Lockard
et al.

Abstract: Traumatic brain injury (TBI) results from direct penetrating and indirect non-penetrating forces that alters brain functions, affecting millions of individuals annually. Primary injury following TBI is exacerbated by secondary brain injury; foremost is the deleterious inflammatory response. One therapeutic intervention being increasingly explored for TBI is hyperbaric oxygen therapy (HBOT), which is already approved clinically for treating open wounds. HBOT consists of 100% oxygen administration, usually betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 129 publications
0
1
0
Order By: Relevance
“…Increased oxygen levels could promote synaptic plasticity and neurotransmission. Also, there are studies that found benefits related to a reduction in cerebral edema, apoptosis, cerebral glucose utilization, vascular density, and synaptic remodeling, each of which has effects on improved functional and cognitive outcomes ( Schimmel et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…Increased oxygen levels could promote synaptic plasticity and neurotransmission. Also, there are studies that found benefits related to a reduction in cerebral edema, apoptosis, cerebral glucose utilization, vascular density, and synaptic remodeling, each of which has effects on improved functional and cognitive outcomes ( Schimmel et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%